The protection of climate refugees under the African human rights system: proposing a value-driven approach (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:The predicament of climate refugees has gained international attention. However, there is no explicit legal protection for them under international law, including African regional law. Their legal protection is not clear. Some scholars and practitioners argue that the existing international framework on refugees does not cover climate refugees. At the African regional level, the 2009 African Union Convention for the Protection and Assistance of Internally Displaced Persons in Africa refers to climate- induced displacement but it does not govern migration beyond borders. This article examines international human rights and refugee law instruments, particularly the 1951 UN Convention Relating to the Status of Refugees and 1969 OAU Convention Governing the Specific Aspects of Refugee Problems in Africa, to identify the challenges and prospects in the legal recognition and protection of climate refugees in Africa. It finds that the gaps existing in the refugee protection regime for climate refugees is historical and continues up to the present. The article consequently argues that the best way to ensure protection for climate refugees in Africa is the operationalising by the AU of its solidarity and humanistic approach as a demonstration of its commitment to the ideals of Pan-African cooperation for addressing common continental problems.TITRE ET RÉSUMÉ EN FRANCAIS:La protection des « refugiés du climat » dans le système africain des droits de l’homme: la proposition d’une approche fondée sur les valeursRÉSUMÉ: La situation précaire des réfugiés climatiques a attiré l’attention de la communauté internationale. Cependant, le droit international, y compris le droit régional africain, ne les protègent pas. Leur protection légale n’est pas claire. Praticiens et doctrinaires sont d’avis que le cadre international existant sur les réfugiés ne couvre pas les réfugiés climatiques. Au niveau régional africain, la Convention de l’Union africaine de 2009 sur la protection et l’assistance aux personnes déplacées en Afrique fait référence au déplacement induit par le climat, mais ne régit pas la migration au-delà des frontières. Cette contribution examine les instruments internationaux relatifs aux droits de l’homme et au droit des réfugiés, en particulier la Convention des Nations Unies de 1951 relative au statut des réfugiés et la Convention de l’OUA de 1969 régissant les aspects spécifiques des problèmes des réfugiés en Afrique, afin d’identifier les défis et les perspectives de la reconnaissance et de la protection juridiques des réfugiés climatiques en Afrique. La contribution constate que les lacunes existant dans le régime de protection des réfugiés climatiques sont historiques et se perpétuent jusqu’à présent. Par conséquent, cette contribution estime que le meilleur moyen d’assurer la protection des réfugiés climatiques en Afrique est la mise en œuvre par l’Union africaine de son approche solidaire et humaniste, démontrant ainsi son attachement aux idéaux de la coopération panafricaine visant à résoudre les problèmes continentaux communs.
Keywords: climate change; climate refugees; international human rights law; refugee protection; refugee law; solidarity